Increasing the sensitivity of ultrasonic transmission measurements for elastic material parameter estimation - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Claes, Leander; Birk, Carolin; Henning, Bernd (Measurement Science and Technology)
Abstract Ultrasonic transmission measurements can be used for material characterization, as the propagation time of sound waves and thus their velocity depends on the elastic material parameters. Measurement results for the elastic material parameters are acquired non-destructively using ultrasonic transmission measurements of hollow cylindrical polymer specimens. To determine the material parameters, an inverse approach is used comparing measurements with simulated data. Previous studies show that the procedure exhibits low sensitivity with respect to the shear parameters of the material. In order to increase the sensitivity, we propose to apply a spatially annular excitation on the base of the specimen. As a measure to analyse the sensitivities with respect to all parameters and their linear independence, we observe the volume of the parallelotope of the sensitivity vectors. Here, a scaled boundary finite element formulation of wave propagation in the specimen is expanded to yield derivative information directly, and a sensitivity analysis can be carried out efficiently. Finally, the results of this sensitivity analysis with regard to the annular excitation are also applied to the measurement setup.
Keywords: Sensitivity analysis; Ultrasonic transducer; Guided waves; Polymers; Gram determinant

Assessment of the influence of curing parameters on fibre reinforced epoxy composite properties using guided ultrasonic waves - Irmak, Hayrettin; Claes, Leander; Wu, Shuang; Marten, Thorsten; Tröster, Thomas (2025 International Congress on Ultrasonics)
The degree of crosslinking in unidirectional prepreg materials was investigated using differential scanning calorimetry to assess their curing behavior and thermal characteristics. To complement these measurements with a non-destructive, in-situ method, the propagation properties of guided acoustic waves in cured carbon fibre-reinforced epoxy plates were analysed. Correlations between the degree of crosslinking and acoustically determined mechanical properties were drawn to enable a future non-destructive evaluation approach.
Keywords: fibre-reinforced polymers; differential scanning calorimetry; degree of crosslinking; guided waves; ultrasound

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)
In this contribution, we present an efficient approach for the transient and time-causal modeling of guided waves in viscoelastic cylindrical waveguides in the context of ultrasonic material characterization. We use the scaled boundary finite element method (SBFEM) for efficient computation of the phase velocity dispersion. Regarding the viscoelastic behavior of the materials under consideration, we propose a decomposition approach that considers the real-valued frequency dependence of the (visco-)elastic moduli and, separately, of their attenuation. The modal expansion approach is utilized to take the transmitting and receiving transducers into account and to propagate the excited waveguide modes through a waveguide of finite length. The effectiveness of the proposed simulation model is shown by comparison with a standard transient FEM simulation as well as simulation results based on the exact solution of the complex-valued viscoelastic guided wave problem. Two material models are discussed, namely the fractional Zener model and the anti-Zener model; we re-interpret the latter in terms of the Rayleigh damping model. Measurements are taken on a polypropylene sample and the proposed transient simulation model is used for inverse material characterization. The extracted material properties may then be used in computer-aided design of ultrasonic systems.
Keywords: viscoelasticity; ultrasonics; guided waves; inverse problem; scaled boundary finite element method